2020
DOI: 10.1002/admt.202000770
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Mushroom Microelectrode Arrays and the Quest for Intracellular‐Like Recordings: Perspectives and Outlooks

Abstract: The ongoing search to decode the brain communication system has propelled major advancements in bioelectronics research. From these, planar microelectrode arrays (MEAs) offer the possibility to record neuronal signals for extremely long periods of time and to probe fundamental principles of learning and adaptation. Unfortunately, MEAs have low neuronal coupling and are thus insensitive to sub‐threshold neuronal signals such as post‐synaptic responses. To surpass this major limitation, a novel category based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 112 publications
0
31
0
Order By: Relevance
“…The realization that the use of substrate integrated planar MEA technologies for extracellular recordings (Figure 1) inherently limits the qualities of in-vitro and in-vivo systems has prompted the development of new 3D in-vitro technologies to enable parallel, multisite intracellular recordings and stimulation from many individual cultured cells (neurons, cardiomyocytes and striated muscles). In principle, this family of in-vitro MEA technologies utilizes different forms of 3D vertical nano-structures (nano-pillars) that pierce the plasma membrane of cultured cells (by electroporation or spontaneously) in a way similar to classical sharp electrodes (Figure 1 and Tian et al, 2010;Angle and Schaefer, 2012;Duan et al, 2012;Gao et al, 2012;Robinson et al, 2012;Angle et al, 2014;Qing et al, 2014;Abbott et al, 2017;Dipalo et al, 2017;Liu et al, 2017;Abbott et al, 2018;Abbott et al, 2019;Mateus et al, 2019;Li et al, 2020;Teixeira et al, 2020;Yoo et al, 2020;Xu et al, 2021;Zhang et al, 2021). At the same time, a number of laboratories have developed the "IN-CELL" recording and stimulation configuration, in which micrometer-sized, extracellular gold mushroom-shaped microelectrodes (gMμEs) record attenuated synaptic and action potentials (Figure 1 and Spira et al, 2007;Hai et al, 2010b;a;Fendyur and Spira, 2012;Spira and Hai, 2013;Rabieh et al, 2016;Shmoel et al, 2016;Weidlich et al, 2017;McGuire et al, 2018;Spira et al, 2018;Mateus et al, 2019;Spira et al, 2019;…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The realization that the use of substrate integrated planar MEA technologies for extracellular recordings (Figure 1) inherently limits the qualities of in-vitro and in-vivo systems has prompted the development of new 3D in-vitro technologies to enable parallel, multisite intracellular recordings and stimulation from many individual cultured cells (neurons, cardiomyocytes and striated muscles). In principle, this family of in-vitro MEA technologies utilizes different forms of 3D vertical nano-structures (nano-pillars) that pierce the plasma membrane of cultured cells (by electroporation or spontaneously) in a way similar to classical sharp electrodes (Figure 1 and Tian et al, 2010;Angle and Schaefer, 2012;Duan et al, 2012;Gao et al, 2012;Robinson et al, 2012;Angle et al, 2014;Qing et al, 2014;Abbott et al, 2017;Dipalo et al, 2017;Liu et al, 2017;Abbott et al, 2018;Abbott et al, 2019;Mateus et al, 2019;Li et al, 2020;Teixeira et al, 2020;Yoo et al, 2020;Xu et al, 2021;Zhang et al, 2021). At the same time, a number of laboratories have developed the "IN-CELL" recording and stimulation configuration, in which micrometer-sized, extracellular gold mushroom-shaped microelectrodes (gMμEs) record attenuated synaptic and action potentials (Figure 1 and Spira et al, 2007;Hai et al, 2010b;a;Fendyur and Spira, 2012;Spira and Hai, 2013;Rabieh et al, 2016;Shmoel et al, 2016;Weidlich et al, 2017;McGuire et al, 2018;Spira et al, 2018;Mateus et al, 2019;Spira et al, 2019;…”
Section: Introductionmentioning
confidence: 99%
“…In principle, this family of in-vitro MEA technologies utilizes different forms of 3D vertical nano-structures (nano-pillars) that pierce the plasma membrane of cultured cells (by electroporation or spontaneously) in a way similar to classical sharp electrodes (Figure 1 and Tian et al, 2010;Angle and Schaefer, 2012;Duan et al, 2012;Gao et al, 2012;Robinson et al, 2012;Angle et al, 2014;Qing et al, 2014;Abbott et al, 2017;Dipalo et al, 2017;Liu et al, 2017;Abbott et al, 2018;Abbott et al, 2019;Mateus et al, 2019;Li et al, 2020;Teixeira et al, 2020;Yoo et al, 2020;Xu et al, 2021;Zhang et al, 2021). At the same time, a number of laboratories have developed the "IN-CELL" recording and stimulation configuration, in which micrometer-sized, extracellular gold mushroom-shaped microelectrodes (gMμEs) record attenuated synaptic and action potentials (Figure 1 and Spira et al, 2007;Hai et al, 2010b;a;Fendyur and Spira, 2012;Spira and Hai, 2013;Rabieh et al, 2016;Shmoel et al, 2016;Weidlich et al, 2017;McGuire et al, 2018;Spira et al, 2018;Mateus et al, 2019;Spira et al, 2019;Jones et al, 2020;Teixeira et al, 2020). Ultrastructural imaging complemented by electrophysiology and model system analysis of the culturedneurons/gMμEs configuration have revealed that the biophysical principles of "IN-CELL" recordings are identical to those of the perforated patch electrode configuration…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, they have enabled transmembrane voltage recordings in excitable cells. [109][110][111][112][113] At the microscale, the patch clamp electrode is recognized for its highly sensitive intracellular voltage recording and its ability to measure current in single ion channels, but it can be tiresome and is usually limited to a few neurons per experiment. Moreover, it is challenging to fabricate patch clamp electrodes into dense arrays; therefore, they cannot be used to interrogate a large area of neural activity, which is a key technological goal in neurobiology.…”
Section: Micro-and Nano-electrode Arraysmentioning
confidence: 99%